Effect of Nigella Seed Extract on Oxidative Stability of Refined Sunflower Oil - KIRALAN, MUSTAFA; BAYRAK, ALI; CALIKOGLU, EDA (Asian Journal of Chemistry, 2010)
Alcohol extracts from nigella seed were added to refined sunflower oil which was oxidized at various temperatures (ambient temperature, 60 and 110 ºC). Oxidation was followed by active oxygen method, Schaal Oven test and specific absorptivity at 232 nm. All of nigella extracts (500, 1000, 2000 ppm) showed antioxidant activity with regard to active oxygen method results. While nigella seed extract of 500 and 1000 ppm have shown antioxidant activity, 2000 ppm application showed prooxidant activity in Schaal oven test. At ambient temperature, oxidation was followed by peroxide value and 1000 ppm nigella seed extract showed strong antioxidant activity during 12 weeks. The study showed that nigella seed extract retarded oxidation of sunflower oil and may be used as a good natural antioxidant source.